Analysis of liquidity, leverage, and inflation on firm value in energy sector companies - Suryani, Dedeh; Suyanto, Suyanto; Jayadi, Jayadi; Oktora, Idham Maulana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Companies generally strive to enhance their value to maximize profits and shareholder wealth. The Firm Value is shaped by multiple factors, including internal aspects like financial performance and external influences such as inflation, which can impact market perception of asset value and the company's future potential. A company's financial performance, including liquidity, leverage, and dividend policy, directly impacts its valuation. Firms with strong financial performance generally achieve higher valuations. This study investigates the impact of liquidity, leverage, and inflation on firm value, with dividend policy acting as a moderating variable. The study targets energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023. Out of a total population of 87 companies, 13 met the criteria for sampling. The findings indicate that liquidity and inflation positively affect firm value, leverage has no significant impact, and dividend policy does not act as a moderating factor in the relationship between liquidity, leverage, and inflation with firm value.